Revolutionary feminists : the women's liberation movement in Seattle - Winslow, Barbara, 1945- (Duke University Press, 2023)
"Revolutionary Feminists tells the story of the radical women's liberation movement in Seattle during the 1960s and 1970s from the perspective of one of its founding members, Barbara Winslow. Drawing on her collection of letters, pamphlets, and photographs as well as newspapers accounts, autobiographies, and interviews, she emphasizes the vital role that Black women played in the women's liberation movement to create meaningful intersectional coalitions in an overwhelmingly White city. Winslow brings the voices and visions of those she calls the movement's "ecstatic utopians" to life. She charts their short-term successes and lasting achievements, from organizing women at work and campaigning for subsidized childcare to creating women-centered rape crisis centers, health clinics, and self-defense programs. The movement was central to winning the first popular vote in the United States to liberalize abortion laws. Despite these achievements, Winslow critiques the failure of its White members to listen to Black, Latina, Indigenous, and AAPI feminist activists. Reflecting on the movement's accomplishments and shortcomings, Winslow offers a model for contemporary feminist activism"--